'Birth defects' of photosystem II make it highly susceptible to photodamage during chloroplast biogenesis. Issue 1 (27th February 2019) - Shevela, Dmitry; Ananyev, Gennady; Vatland, Ann K.; Arnold, Janine; Mamedov, Fikret; Eichacker, Lutz A.; Dismukes, G. Charles; Messinger, Johannes
Abstract : High solar flux is known to diminish photosynthetic growth rates, reducing biomass productivity and lowering disease tolerance. Photosystem II (PSII) of plants is susceptible to photodamage (also known as photoinactivation) in strong light, resulting in severe loss of water oxidation capacity and destruction of the water‐oxidizing complex (WOC). The repair of damaged PSIIs comes at a high energy cost and requires de novo biosynthesis of damaged PSII subunits, reassembly of the WOC inorganic cofactors and membrane remodeling. Employing membrane‐inlet mass spectrometry and O2 ‐polarography under flashing light conditions, we demonstrate that newly synthesized PSII complexes are far more susceptible to photodamage than are mature PSII complexes. We examined these 'PSII birth defects' in barley seedlings and plastids (etiochloroplasts and chloroplasts) isolated at various times during de‐etiolation as chloroplast development begins and matures in synchronization with thylakoid membrane biogenesis and grana membrane formation. We show that the degree of PSII photodamage decreases simultaneously with biogenesis of the PSII turnover efficiency measured by O2 ‐polarography, and with grana membrane stacking, as determined by electron microscopy. Our data from fluorescence, Q B ‐inhibitor binding, and thermoluminescence studies indicate that the decline of the high‐light susceptibility of PSII to photodamage is coincident with appearance of electron transfer capability Q A − → Q B during de‐etiolation. This rate depends in turn on the downstream clearing of electrons upon buildup of the complete linear electron transfer chain and the formation of stacked grana membranes capable of longer‐range energy transfer.